Pengaruh Efikasi Diri, Motivasi, dan Pemanfaatan Media Sosial Terhadap Minat Berwirausaha pada Generasi Z di Wilayah Kota Surabaya Timur - Pratama, Eva Agustin; Nasution, Ute Ch.; Andayani, Sri (Research Journal of Social Science and Economics, 2025)
This study aims to determine whether the variables of Self-Efficacy, Motivation and Social Media Utilization affect Entrepreneurial Interest in Generation Z in the East Surabaya City Region, the number of samples used was 100 people who were all Generation Z in East Surabaya using non-probability sampling techniques. The data collection process uses a questionnaire filled out by employees using a Likert scale as a measurement tool. This research includes quantitative research, the analysis method used is multiple linear regression analysis, classical assumption test, validity test, and reliability test. Hypothesis collection techniques using t test, F test, and coefficient of determination. The results of this study indicate that simultaneously all independent variables have a positive and significant effect on entrepreneurial interest in Generation Z in East Surabaya. The results partially variable Self-efficacy, Motivation and Social Media Utilization have a positive and significant effect on Entrepreneurial Interest in Generation Z in East Surabaya. The results of the coefficient of determination (R²) obtained by 48.0% which is the influence of the variables of Self-Efficacy, Motivation and Social Media Utilization, the rest is influenced by other variables outside this study, such as capital, family environment etc.